Desperately seeking the primary: a systematic approach to assessing malignant cervical lymphadenopathy. Issue 5 (May 2022) - Robinson, Max; Okpokam, Atuora; Sandison, Ann
Abstract: Cervical lymphadenopathy is a common sign of disease in the head and neck region with a wide differential diagnosis. The most common causes are a consequence of infection. Malignancy is usually due to metastasis from a head and neck squamous cell carcinoma and viral testing for human papillomavirus and Epstein–Barr virus can be used to direct the search for the primary to the oro-pharynx and nasopharynx respectively. Whilst metastatic adenocarcinomas may arise from the salivary and thyroid glands, metastasis from a distant primary should also be considered. In these cases, cytokeratins 7 and 20 are used to narrow the differential diagnosis. Undifferentiated malignancies may require extended immunohistochemical panels and molecular tests to render a diagnosis. Rarely, no primary tumour is discovered and the diagnosis of 'cancer of unknown primary' (CUP) is assigned. In the future, genetic analysis will become increasingly important in predicting the tissue of origin and informing treatment options.